PRACTICES OF MANAGING STUDENTS' DIVERSITY OF RESIDENTIAL STATUS AND ACHIEVEMENT OF EDUCATIONAL GOALS IN MAKERERE UNIVERSITY (UGANDA) - Mukisa, Elizabeth Juliet; Musoke, Dr. Gyaviira Genza; Kimoga, Joseph (African Journal of Education and Practice, 2021)
Purpose: The Purpose of the study was to explore the management practices that govern students' residential affairs that enable the pursuit of educational goals in Makerere University. The research objective that guided the study was how management practices regarding residential affairs enabled or disabled on-campus and off-campus students to pursue their educational goals. Methodology: Cushioned by the social justice literature we inquired on how Makerere University managed students' residential affairs and how such management practices supported the students to achieve their educational goals. We adopted a qualitative approach informed by comparative phenomenological design. A purposive sampling technique was used to obtain 8 informants drawn from the science and humanities schools. Data was analysed qualitatively using thematic analysis. Findings: The study found out that management practices such as allocation and flexibility regarding residential affairs enabled pursuit of educational goals. However, absence of regular supervision contributed to poorly maintained halls of residence, toilets and bathrooms are filthy, dilapidated rooms, poor security and meals. These acted as barriers in the way the students pursued their educational goals. Contribution to theory, practice and policy: the findings and discussion will contribute to the knowledge required for managing students' residential affairs for Makerere University and other higher learning institutions through formulation and implementation responsive strategies for convenience that enable students to accomplish their educational goals.